Key Performance Indicator Implementation Training for Cattle Ranchers in Nagori Bahjoga Village - Taufiq Risal; Austin Alexander Parhusip; Tika Nirmala Sari; Wisnu Rayhan Adhitya; Fitri Yani (STMIK Pontianak, 2021)
This activity departs from the problem that we noticed that the number of local cattle farmers could not compete with imported cattle farms owned by large companies. To measure how far the strategy that the organization has done to achieve the vision and mission, therefore it takes a Key Performance Indicator (Key Performance Indicator) which at the same time serves as a measuring tool and measuring to where the vision and mission of the organization is achieved. The target audience of this devotion is Cattle Rancher in Nagori Bahjoga Village of Simalungun Regency. Devotional activities are followed by cattle farmers in Nagori Bahjoga Village, From the evaluation results obtained results and benefits of this devotional activity including this training, the cattle group gained knowledge about key performance indicators that can improve the performance of cattle farmers, participants know what are the steps in the key performance indicator, participants understand and run key performance indicators and participants feel the benefits in make it easier for HRD to make measurements and evaluations of employee performance and their impact on company performance